Pengaruh Kelas Remaja Putri Dan Integrasi Model Aplikasi Android "My Periode Tracker" Untuk Menurunkan Gejala Kecemasan Premenstrual Syndrome - Alice Leiwakabessy; Henny Novita; Endah Dian Marlina; Ayi Tansah Rohaeti; jusuf Kristianto (Jurnal Health Sains, 2022)
psychological changes called Premenstrual Syndrome (PMS). Approximately 75% occurs in women of reproductive age, including adolescent girls. This situation can cause teenagers to experience problems in terms of achievement in school and social relationships with peers or disruption of daily activities if PMS is not handled properly. To reduce PMS symptoms, several strategies can be used, including stress management and complementary therapies such as yoga and breathing exercises that have been developed into a website-based application. This research was conducted by taking data from Al Hidayah Vocational High School students in South Jakarta who were given treatment in the Young Women class and monitoring PMS symptoms using the "Premenstrual Syndrome Tracker" application for the intervention group and the control group who were given counseling. The design of this study used a Quasi Experimental Group with Pretest-Pottest Control Design. In this design, there are two groups, each of which is selected randomly, one group acts as a control and the other group as an intervention group. The treated group is called the intervention group. Then, at the specified time, the intervention group was given treatment. After the treatment was completed, measurements were made for both groups. Comparison of results between the two groups shows the effect of the treatment that has been given. The number of respondents was 60 people, consisting of 30 control groups and 30 intervention groups. The conclusion of the study using this application to reduce the symptoms of premenstrual syndrome showed positive results. The results of the study reflect that young women say that the applications they use are able to empower them and provide knowledge and are more aware and aware of their menstrual cycles, they can also find out about menstrual cycle irregularities and how to overcome physical and psychological discomfort before and during menstruation. can be used as information for health workers.